PENILIAN KINERJA GURU DI SEKOLAH DASAR, ANTARA TANTANGAN DAN PELUANG - Alvi Syafaatu Rosidah; Wahyu Izza Rahman; Maharani Aulia; Ariansyah Ariansyah; Imron Fauzi (DIMAR: Jurnal Pendidikan Islam, 2022)
Based on Law Number 57 of 2021 concerning Teacher Performance Standards, National Education aims to educate the nation by improving the quality of teachers, therefore there is a need for teacher performance assessments that aim to determine the ability or expertise of each teacher so that teachers can carry out their duties professionally. Teacher performance is an achievement that can be measured through predetermined and mutually agreed standards. Teacher Performance Standards are related to the quality of teachers in carrying out their duties such as being a teacher who makes students feel at home in class, understanding preparation and design of learning assessments, being able to apply interesting and not boring learning media, being able to create a lively classroom atmosphere by involving students in various activities. learning experience and being a strict teacher when learning is not appropriate. This article aims to explain the importance of teacher performance and motivation to achieve teacher performance appraisal. Teaching is a noble job, because the teaching profession is very well known among the public for its patience in dealing with students. There are several obstacles or obstacles in assessing teacher performance, one of which is an unclear standard due to inconsistent and changing standards so that it can affect teacher achievement. In addition to obstacles, there are opportunities for teacher performance, namely the achievement of teacher quality so that it can be said to be a professional teacher. Teacher Performance Assessment can improve the ability of teachers in Indonesia.